To solve the equation \(3x^2 - 7 = 20\) by factoring, we first need to rearrange the equation into standard form.
-
Subtract 20 from both sides of the equation:
\[ 3x^2 - 7 - 20 = 0 \]
This simplifies to:
\[ 3x^2 - 27 = 0 \]
-
Next, we can factor out the common factor (which is 3):
\[ 3(x^2 - 9) = 0 \]
-
Now, we can set the equation inside the parentheses to zero:
\[ x^2 - 9 = 0 \]
-
Notice that this is a difference of squares, which can be factored further:
\[ (x - 3)(x + 3) = 0 \]
-
Now we can find the solutions by setting each factor equal to zero:
\[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \]
\[ x + 3 = 0 \quad \Rightarrow \quad x = -3 \]
Thus, the correct solutions to the equation \(3x^2 - 7 = 20\) are:
\[ x = 3 \quad \text{and} \quad x = -3 \]